Images de la femme dans l'oeuvre litteraire de Sembene Ousmane - Vrancken, Maria do Céu Oliveira (French Language and Literature, 2017)
One of the main reasons, for the Senegalese author Sembene Ousmane's prominence in African literature of French expression is that he, more than any other male African author, has sought to give to the female characters in his literary works an important role in African Society. This thesis analyses the female characters in Sembene's literary works with the aim of evaluating their importance, the author's attitude towards them and finally Sembene's feminism. The first five chapters analyse the female characters in different contexts, namely marriage, the family, work, politics and religion. the sixth chapter studies the usually avoided subject of the dissolute woman. The last chapter deals with the place given to women in Sembene's writing, ie. the comparison between the number of male and female characters and the narrative techniques which he utilizes to characterize the latter.